1987
DOI: 10.1007/bf00396383
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive and endocrine gonadal capacity in patients treated with COPP chemotherapy for Hodgkin's disease

Abstract: Testicular and ovarian functions were assessed in 33 patients with Hodgkin's disease 1 to 17 years after cessation of COPP chemotherapy with cyclophosphamide, vincristine, procarbazine, prednisone. Diagnostic procedures consisted of hormone measurements, interviews, and semen analyses. In women serum levels of follicle-stimulating hormone (FSH), luteinizing hormone (LH), 17 beta-estradiol, progesterone, prolactin, and in men FSH, LH, 17 beta-estradiol, testosterone, and prolactin were determined. Semen analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
0
4

Year Published

1989
1989
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(45 citation statements)
references
References 22 publications
4
32
0
4
Order By: Relevance
“…Similar results have been reported elsewhere 17,22,24 and confirm the hypothesis that spermatogonia are sensitive to chemotherapy, whereas Sertoli and Leyding cells are more resistant. 16,34 Since increased FSH serum levels have been associated with germinal epithelial damage, our findings support the hypothesis that male infertility after treatment is at least in part due to germinal epithelial damage. 22,26 Although FSH levels were elevated after treatment, there was no statistically significant correlation between FSH levels and fertility status, probably due to the small number of patients in our cohort.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Similar results have been reported elsewhere 17,22,24 and confirm the hypothesis that spermatogonia are sensitive to chemotherapy, whereas Sertoli and Leyding cells are more resistant. 16,34 Since increased FSH serum levels have been associated with germinal epithelial damage, our findings support the hypothesis that male infertility after treatment is at least in part due to germinal epithelial damage. 22,26 Although FSH levels were elevated after treatment, there was no statistically significant correlation between FSH levels and fertility status, probably due to the small number of patients in our cohort.…”
Section: Discussionsupporting
confidence: 83%
“…Similar rates of azoospermia after treatment were also reported with older regimens such as MVPP (mechlorethamine, vinblastine, procarbazine, and prednisone; 88%; 36 of 41 patients), MOPP (86%; 25 of 29 patients), and COPP (100%; 19 of 19 patients). 16,25,26 There are some indications that fertility is more often preserved with MOPP/ABVD compared with MOPP. 27 The cumulative dose of the cytostatic drugs given seems to be one of the key determinants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10 The information on the effects of chemotherapy on early menopause, however, is still limited. Studies suffer from several shortcomings, including small sample size [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] and lack of detailed information on treatment exposures. 29,30 Although in most cases only acute gonadotoxic effects and chemotherapy-related amenorrhea have been studied rather than long-term effects on premature menopause, it can be concluded that alkylating agents are the most hazardous chemotherapeutic agents, and that gonadotoxicity is dose dependent.…”
Section: Introductionmentioning
confidence: 99%